A genetically encoded small-size fluorescent pair reveals allosteric conformational changes of G proteins upon its interaction with GPCRs by fluorescence lifetime based FRET. Issue 51 (21st May 2020) - Shi, Pan; Zhang, Yanan; Lv, Pei; Fang, Wei; Ling, Shenglong; Guo, Xiaoqi; Li, Dong; Liu, Sanling; Sun, Demeng; Zhang, Longhua; Liu, Dongsheng; Zheng, Ji-Shen; et al.
Abstract : A genetically encoded small-size fluorescent pair to reveal the conformational changes of G proteins upon binding GPCRs by fluorescence lifetime based FRET. Abstract : The dynamics of GPCRs (G protein-coupled receptors) coupling for cognate G proteins play a critical role in signal transduction. Herein, we reported a site-specifically labelled small-sized fluorescent pair 7-HC/FlAsH ((7-hydroxycoumarin-4-yl)-ethylglycine/fluorescein arsenical hairpin) for fluorescence lifetime based FRET (fluorescence resonance energy transfer) to reveal conformational differences of Gαi1 (inhibitory G proteins) and Gαs (stimulatory G proteins) upon β2 AR (β2 -adrenergic receptor) coupling. It offers a new generally applicable method to probe protein dynamic interactions or conformational changes.